Acculturation of Knowledge through Sustainable Language Engineering for National Development: The Case of Igbo - Obianika, Chinwe E.; Onu, Mercy Agha (European Scientific Journal, ESJ, 2016)
The aim of this study is to find out the possible ways of domesticating knowledge gained through western education by the Igbo through sustainable language development. It also aims to make the knowledge accessible in the Igbo language for empowerment at the grassroots and ultimately for societal and national development. The need for this work is born out of the observation that the Igbo, as well as other tribes in Nigeria are rich with internationally acclaimed learned personalities. These personalities have distinguished themselves in various fields of human endeavor. Also, these achievements are made in foreign languages. Subsequently, these achievements have led to an increase in the relevance of such languages to the relegation of the scholars’ own mother tongues and invariably their own people. By using the descriptive and inferential methods, the paper presents some neologism processes which non linguists can apply in their various academic fields. Also, they can come up with terminologies in the Igbo language for presenting relevant academic materials for use in teaching and learning the Igbo language. The use of these terminologies could be formal or informal as the need arises. Thus, these processes include extra-language borrowing, loan translations, intra-language borrowing, and specialization of dialectal phonological variants. Previously, metalanguage development efforts by governments had bypassed these professionals. Also, they have focused on developing the terminologies through linguists and selected professionals alone. This has resulted to the terminologies not being accessible to the intended end users. Among other things, this paper suggests that the call for the acculturation of knowledge and the processes of embarking on it should be made public in all institutions of higher education. This is carried out in the Igbo culture area and later extended to the Igbo in diaspora. However, the co-ordination of the process of the formalization of the terminologies should be left in the hands of the Igbo Studies Association (ISA). This official regulating body ensures the maintenance of professional standards and uniformity of usage.